Evaluation of violence in health with white code data Elazig Fırat University Hospital example - Albay, Ayşe; Nizam, Feridun (Malatya Turgut Özal Üniversitesi, 2022)
Background: A topic that can be discussed with solutions and opinions about the health education practiced by the students over the Elazig Fırat Hospital white code internet system. Materials and Methods: A total of 180 White Data University Hospital Data was conducted between January 2014 and 2021 retrospectively. IBM SPSS Statistic 22 package program was used in the analysis of the data. Chi-square (chi-square) engineering is applied while animating the data. This analysis was, and the interpretation was based on a p<0,05 point level. Results: In the study, between the years 2014-2021, the year in which violence in health was most common was 2017 (23%), the violence was mostly carried out between 08.00-17.00 (52.2%), female workers (63%) were exposed to violence more, the most exposed to violence. The remaining professional group is research assistants (58%), the most common type of violence is verbal violence (69%), the perpetrators are mostly relatives of patients (83%) and men (75%), the rate of perpetrators of violence being taken into custody is quite low. (5%) and violence occurred more frequently in emergencies (35%). Conclusions: In the study, as health workers, women are exposed to violence more and they are mostly exposed to verbal violence, the violence is mostly carried out by patients' relatives and men, the occupational group that is most exposed to violence is physicians and nurses who are in direct contact with the patient, violence events are more common in emergency units. It has been concluded that the type of violence applied varies according to gender and the type of violence does not vary according to the place where the incident took place.

Amaç: Elazığ Fırat Üniversitesi Hastanesi beyaz kod internet sistemi verileri ışığında sağlıkta şiddetin analizini yaparak konu hakkında çözüm önerileri sunmak ve alınabilecek önlemlerin geliştirilmesine katkı sağlamak amaçlanmıştır. Materyal ve Metot: Ocak 2014 ile Aralık 2021 tarihleri arasında Fırat Üniversitesi Hastanesine yapılan toplam 180 Beyaz Kod verisi retrospektif olarak incelenmiştir. Verilerin analizinde IBM SPSS Statistic 22 paket programı kullanılmıştır. Verilerin analizi gerçekleştirilirken çalışmanın amaçları doğrultusunda frekans ve yüzde, ki-kare (chi-square) testleri kullanılmıştır. Bu analiz sonuçlarının yorumlanmasında ise p<0,05 anlamlılık düzeyi esas alınmıştır. Bulgular: Çalışmada 2014-2021 yılları arasında sağlıkta şiddetin en çok görüldüğü yılın 2017 (%23) olduğu, şiddetin yoğunlukla 08.00-17.00 (%52,2) saatleri arasında gerçekleştirildiği, kadın çalışanların (%63) daha çok şiddete maruz kaldığı, şiddete en çok maruz kalan meslek grubunun araştırma görevlilerinin (%58) olduğu, en çok uygulanan şiddet türünün sözel şiddet (%69) olduğu, şiddeti uygulayan kişilerin çoğunlukla hasta yakınları (%83) ve erkeklerden (%75) oluştuğu, şiddeti uygulayanların göz altına alınma oranlarının oldukça düşük (%5) olduğu ve şiddetin acillerde (%35) daha fazla gerçekleştiği görülmüştür. Sonuç: Çalışmada sağlık çalışanları olarak kadınların daha çok şiddete maruz kaldığı ve yoğunlukla sözel şiddete uğradıkları, uygulanan şiddetin yoğunlukla hasta yakını ve erkekler tarafından gerçekleştirildiği, şiddete en çok maruz kalan meslek grubunun hasta ile doğrudan iletişim halinde olan hekimler ile hemşireler olduğu, şiddet olaylarının acil ünitelerinde daha sık gerçekleştiği, uygulanan şiddet türünün cinsiyete göre değişkenlik gösterdiği ve şiddet türünün olayın gerçekleştiği yere göre değişkenlik göstermediği sonuçlarına ulaşılmıştır.
Sağlıkta şiddetin beyaz kod verileri ile değerlendirilmesi Elazığ Fırat Üniversitesi Hastanesi örneği
Keywords: Primary Health Care; Birinci Basamak Sağlık Hizmetleri